2020
DOI: 10.1093/heapol/czaa107
|View full text |Cite
|
Sign up to set email alerts
|

Do social accountability approaches work? A review of the literature from selected low- and middle-income countries in the WHO South-East Asia region

Abstract: Governance failures undermine efforts to achieve universal health coverage and improve health in low- and middle-income countries by decreasing efficiency and equity. Punitive measures to improve governance are largely ineffective. Social accountability strategies are perceived to enhance transparency and accountability through bottom-up approaches, but their effectiveness has not been explored comprehensively in the health systems of low- and middle-income countries in south and Southeast Asia where these str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…Another area of frequently used social accountability interventions was access to health care. SA interventions facilitating the interaction between service providers and clients could improve access and health outcomes ( 30 ). When the people are able to express their priorities and make policy makers accountable for addressing their needs it will increase access, which could be increasing the working hours of health facilities as well decreasing absenteeism of health workers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another area of frequently used social accountability interventions was access to health care. SA interventions facilitating the interaction between service providers and clients could improve access and health outcomes ( 30 ). When the people are able to express their priorities and make policy makers accountable for addressing their needs it will increase access, which could be increasing the working hours of health facilities as well decreasing absenteeism of health workers.…”
Section: Discussionmentioning
confidence: 99%
“…There is no standard and fit-for-all-purpose tool for social accountability. The success of these measures is highly dependent on the context of the country, capacities, information, the range of different actors the independence of the people from power and leadership have been effective ( 30 ). Therefore, the study of power relations is important in the analysis of social accountability ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the raised levels of agency in the community supported greater social accountability of the local health services. To date, several mechanisms have been considered to enhance social accountability, including community action groups, social audits, score cards, and so on [ 42 ], but social innovation appears to be a mechanism to achieve greater social accountability within communities.…”
Section: Discussionmentioning
confidence: 99%
“…While leadership and governance are hinged on the context, capacity, information, and the spectrum of actor involvement, the overarching principle can be observed through the experience, including policy guidance, intelligence and oversight, collaboration and coalition building, regulation, system design, and accountability (WHO, 2007 ; Naher et al. , 2020 ). Our study revealed only the partial aspects of leadership and governance – health programme management and human resources – since the participants were the frontline healthcare workers, holding limited experiences and views about the governance system.…”
Section: Discussionmentioning
confidence: 99%